Ureasil-polyether hybrid film-forming materials - Souza, L. K. [UNESP]; Bruno, C. H. [UNESP]; Lopes, L. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Chiavacci, L. A. [UNESP] (Elsevier, 2013)
The objectives of this work were to study the suitability and highlight the advantages of the use of cross-linked ureasil-polyether hybrid matrices as film-forming systems. The results revealed that ureasil-polyethers are excellent film-forming systems due to specific properties, such as their biocompatibility, their cosmetic attractiveness for being able to form thin and transparent films, their short drying time to form films and their excellent bioadhesion compared to the commercial products known as strong adhesives. Rheological measurements have demonstrated the ability of these hybrid matrices to form a film in only a few seconds and Water Vapor Transmitting Rate (WVTR) showed adequate semi-occlusive properties suggesting that these films could be used as skin and wound protectors. Both the high skin bioadhesion and non-cytotoxic character seems to be improved by the presence of multiple amine groups in the hybrid molecules. © 2012 Elsevier B.V.
Keywords: Film-forming material; Hybrid materials; Sol-gel; Amine groups; Bio-adhesion; Commercial products; Drying time; Film-forming; Film-forming materials; Hybrid matrix; Hybrid molecules; Rheological measurements; Transparent films; Biocompatibility; Ethers; Polyethers; Sol-gels; amine; biomaterial; cross linking reagent; polyether; unclassified drug; ureasil; animal tissue; biocompatibility; biofilm; flow kinetics; human; human cell; molecular weight; nonhuman; priority journal; tissue adhesion; water vapor; Adhesiveness; Animals; Biocompatible Materials; Catalysis; Cell Survival; Cross-Linking Reagents; Drug Delivery Systems; Drug Industry; Gels; Hydrogen-Ion Concentration; Permeability; Polyethylene Glycols; Propylene Glycols; Rheology; Swine; Urea; Water; Water Loss, Insensible